Emerging Low‐Dimensional Heterostructure Devices for Neuromorphic Computing. Issue 10 (17th July 2022) - Liang, Shi-Jun; Li, Yixiang; Cheng, Bin; Miao, Feng
Abstract : Over the last few decades, advance in material science has made it possible to control the dimensions of materials structures with atomic scale precision and to realize various low‐dimensional heterostructures. These heterostructures have been widely used in the electronic and spintronic as well as optoelectronic devices, with great success. Engineering the dimensionality and physical properties of low‐dimensional materials enables to design a large variety of low‐dimensional artificial heterostructures. The inherent physical properties that these emerging low‐dimensional heterostructures exhibit open unprecedented opportunities for neuromorphic computing applications, e.g., neuromorphic electronics, neuromorphic spintronics, and neuromorphic optoelectronics, which lay the foundation for building up intelligent system in the future. Herein, the current main status of the emerging low‐dimensional heterostructures used in neuromorphic electronic, neuromorphic spintronic, and neuromorphic optoelectronic devices is reviewed, and the relevant challenges and outlook for future advances are discussed. Abstract : The diverse properties of the emerging low‐dimensional heterostructures open unprecedented opportunities for various types of neuromorphic devices inaccessible in conventional bulk heterostructures. Research progress of low‐dimensional heterostructures applications in neuromorphic electronic and spintronic as well as optoelectronic devices is reviewed, together with relevant discussion on the challenges and opportunities in the future development of neuromorphic devices.